THE USE OF ETHNIC LANGUAGES IN INTER AND INTRA ETHNIC COMMUNICATION IN DESA LAWE TAWAR ACEH TENGGARA-ACEH PROVINCE - Rasmita Br Karo; Berlin . Sibarani; Siti Aisyah Ginting (Universitas Negeri Medan, 2022)
The objective of the study was to elaborate the factor cause of ethnic language use by the people in inter and intra ethnic communication in Lawe Tawar. A qualitative descriptive research design was applied. The data of this study were words, phrases consist of inter and intra ethnic communication which is uttered by the people in Lawe Tawar. The subject of this research were Batak Toba ethnic, Karo ethnic, Simalungun ethnic, Pak-Pak ethnic and Nias ethnic at the age 18-50 years old. The instruments used for this study were observation and in-depth interview. The data was analyzed by using interactive models of Miles & Huberman (2014:8) technique. The results of the study show some factors of people used the language choice in inter and intra ethnic communication, they were: (1)Ethnic Background of the Participants, (2)Extent of Intimacy with the Interlocutor, (3)Different Social Status of the Participant,(4) Equal Social Status,(5) Showing Off One’s Ethnic Language Mastery. Meanwhile the factors of people in language choice in intra ethnic such as: (1) Ethnic Background of the participant, (2) Immigration, (3) The Topic Discussed